Estudo físico-químico e eletroquímico de polímeros e copolímeros derivados do tiofeno beta-substituído - Marcos Roberto de Abreu Alves (2009)
This work presents the synthesis and characterization of several homopolymers and copolymers derived from beta-substituted thiophene as well as the effect of substituent groups on the properties of materials. With this purpose, the studies were conducted in three stages.In the first step of the work the synthesis of the monomers 3-acetoxymetylthiophene and 3-(2-acetoxyethyl)thiophene were done starting from the acetylation of the corresponding alcohols as well as the optical and the spectroscopic characterization of them. Besides the obtained commercially monomers (3-methoxythiophene, 3-thiophenemethanol, 3-thiopheneethanol, 3-thiophenecarboxílicacid and ethyl 3-thiopheneacetate were also studied using spectroscopy techniques such as infrared (IR) and ultraviolet-visible (UV-vis) and one dimensional Nuclear Magnetic Resonance (NMR 1H, 13C and Dept135).The second part was devoted to chemical synthesis of the homopolymers: poly(3-methoxythiophene) (PMOT), poly(3-thiophenemethanol) (PTM), poly(3-thiopheneethanol) (PTE), poly(ethyl 3-thiopheneacetate) (PTAE), poly(3-acetoximethylthiophene) (PAMT) and poly(3(2-acetoxyethyl)thiophene) (PAET); and of the copolymers: poly(3-methoxythiophene-co-3-thiopheneethanol) (PMOT-co-TE), poly(3-methoxythiophene-co-3-thiophenemethanol) (PMOT-co-TM), poly(3-methoxythiophene-co-3-thiophenecarboxilic acid) (PMOT-co-ATC), poly(3-methoxythiophene-co-ethyl 3-thiopheneacetate) (PMOT-co-TAE), poly(3-methoxythiophene-co-3-acetoxymetylthiophene) (PMOT-co-AMT), poly(3-methoxythiophene-co-3(2-acetoxyethyl)thiophene) (PMOT - co-AET). The chemical syntheses were done using the oxidative coupling method with ferric chloride (FeCl3). Several techniques were employed for characterization, such as the photoluminescencewhich showed very proved promising results for the development of novel optical devices. The third part was of the synthesis of PMOT homopolymer and copolymers of poly(3-methoxythiofene-co-3-thiopheneethanol) (PMOT-co-TE), poly(3-methoxythophene-co-3-thiophennemethanol) (PMOT-co-TM) and poly(3-methoxythiophene-co-3-thiophenecarboxilic acid) (PMOT-co-ATC) byelectrochemistry employing the chronoamperometry as electropolymerization technique. Spectrometric studies by UV-vis, IR, gel permeation chromatography (GPC) and cyclic voltammetry (CV) were employed in their characterizations and interesting and very promising properties were observed.